Contribuições das práticas de governança corporativa no alinhamento estratégico entre tecnologia da informação e negócio: estudo de caso em uma instituição paraestatal de educação - Menezes, Clarissa Braz (Universidade do Vale do Rio dos Sinos, 2012)
Emerged a few decades ago, the Corporate Governance theme has gained prominence since the financial scandals in U.S. corporations that occurred at the end of 2001 and repeated in 2008. The misleading information, that caused financial losses when they became public, resulted in profound shock in market confidence, which has important need for greater transparency in management practices and in the information disclosed to the company. This research examined the effects of corporate governance practices in strategic alignment business-IT, in an organization. We sought to examine whether the corporate governance practices, imbued with Neo-Institutional and Institutional’ Theorys concepts, as isomorphism and legitimacy, can contribute to the strategic alignment of IT, leading the organization to greater transparency and efficiency in the use of public and private resources, resulting in its continuity and sustainability. The survey was conducted through a case study conducted in the context of a nonprofit organization, which provides educational services. The research approach is important because the institution investigated uses information technology in intensive way, both as support areas and business operation. There is a strong dependence on the business area in relation to IT. The survey was conducted in two stages, in the first, more ample, was conducted using a questionnaire sent to all twenty seven Senac’s Administrations in the country. With this instrument were performed interviews at Rio Grande do Sul’s Administration and the consultations in secondary data sources such as documents, records and reports. As a result, it was concluded that the contribution comes from the direct relationship that corporate governance practices identified at Senac have with the promoters of strategic alignment business-IT as well as the role of governance as a facilitator of achievement business and IT goals, as demonstrated at the relation between COBIT® and IBGC. We tried to thereby contribute to organizational studies that address strategy, information technology and corporate governance.
Keywords: Governança corporativa; Alinhamento estratégico de TI ao negócio; Institucionalismo; Corporate governance; Strategic alignment business-IT; Institutionalism; ACCNPQ::Ciências Sociais Aplicadas::Administração